Prevalence, comorbidities, and factors associated with prolonged grief disorder, posttraumatic stress disorder and complex posttraumatic stress disorder in refugees: a systematic review - Franziska Lechner-Meichsner; Hannah Comtesse; Marie Olk (Conflict and Health, 2024)
Abstract Background The number of refugees worldwide is at an all-time high with many being exposed to potentially traumatic events and the loss of loved ones. The 11th revision of the International Statistical Classification of Diseases and Related Health Problems now includes prolonged grief disorder and complex posttraumatic stress disorder and revised criteria for posttraumatic stress disorder. An overview of these stress-related disorders among people who have become refugees is therefore needed. Consequently, we conducted a systematic review to determine prevalence rates, comorbidities, and associated factors for each of the disorders. Method We systematically searched PubMed, Web of Science, and PsycArticles to identify studies that reported prevalence rates, predictors or associated factors, and/or comorbid mental disorders for either (1) prolonged grief disorder, (2) posttraumatic stress disorder, or (3) complex posttraumatic stress disorder among refugees. The selection process followed the PRISMA guidelines. Results A total of 36 studies met the inclusion criteria. Most of the studies were of high quality. There was substantial variation in prevalence rates by disorder, with prolonged grief ranging from 6 to 54%, posttraumatic stress disorder ranging from 0.4 to 80%, and complex posttraumatic stress disorder ranging from 3 to 74.6%. Pooled prevalence for posttraumatic stress disorder was estimated at 29.8% in treatment seeking samples and 9.92% in population samples. For complex posttraumatic stress disorder, it was estimated at 57.4% in treatment seeking samples and 7.8% in population samples. Posttraumatic stress disorder was among the most frequent comorbidities for prolonged grief disorder while depressive symptoms were the most frequently occurring co-morbidity across all three disorders. Sociodemographic variables, trauma exposure, and loss characteristics were associated with higher symptom severity. Postmigration living difficulties played an important role in prolonged grief and complex posttraumatic stress disorder. Conclusion The review revealed substantial differences in prevalence rates between the three studied disorders but underscored a very high prevalence of ICD-11 stress-related disorders among refugees. The identified associated factors point to subgroups that may be particularly at risk and establishes a foundational basis for targeted interventions and potential policy changes. Future research should incorporate longitudinal investigations and emphasize culturally sensitive assessments.